An outbreak of Rift Valley fever in Northeastern Kenya, 1997-98. - Woods, C; Karpati, A; Grein, T; McCarthy, N; Gaturuku, P; Muchiri, E; Dunster, L; Henderson, A; Khan, A; Swanepoel, R; Bonmarin, I; Martin, L; et al. (2002)
In December 1997, 170 hemorrhagic fever-associated deaths were reported in Garissa District, Kenya. Laboratory testing identified evidence of acute Rift Valley fever virus (RVFV). Of the 171 persons enrolled in a cross-sectional study, 31(18%) were anti-RVFV immunoglobulin (Ig) M positive. An age-adjusted IgM antibody prevalence of 14% was estimated for the district. We estimate approximately 27,500 infections occurred in Garissa District, making this the largest recorded outbreak of RVFV in East Africa. In multivariable analysis, contact with sheep body fluids and sheltering livestock in one s home were significantly associated with infection. Direct contact with animals, particularly contact with sheep body fluids, was the most important modifiable risk factor for RVFV infection. Public education during epizootics may reduce human illness and deaths associated with future outbreaks.